2020
DOI: 10.1111/dth.14074
|View full text |Cite
|
Sign up to set email alerts
|

A significant reduction in the diagnosis of melanoma during the COVID‐19 lockdown in a third‐level center in the Northern Italy

Abstract: The human severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic changed the usual care practice worldwide with the necessity to reorganize and postpone the majority of elective most planned medical and surgical activities. 1 Malignant melanoma is the most lethal form of skin cancer. The incidence of melanoma is climbing steadily and peaks at the seventh and eighth decades of life. 2 Old patients, with chronic comorbidities, belong to the same population with a higher risk of SARS-CoV-2 infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 5 publications
5
26
0
Order By: Relevance
“…Disease stage, corresponding to primary tumor thickness, represents the most important prognosis factor; therefore, an early diagnosis is essential for melanoma patients' survival rates (3). The reduction in the number of accesses in dermatological departments during the lockdown caused a reduction in new diagnosis of melanoma and may also lead to undetected or late detection of skin cancers increasing morbidity and mortality in the worldwide population (1,4). Finally, following the reduction of consultations for skin cancer screening during the pandemic period the implementation of screening campaigns and people information in order to increase the awareness of this public health problem should be considered (5).…”
Section: Letter To the Editormentioning
confidence: 99%
“…Disease stage, corresponding to primary tumor thickness, represents the most important prognosis factor; therefore, an early diagnosis is essential for melanoma patients' survival rates (3). The reduction in the number of accesses in dermatological departments during the lockdown caused a reduction in new diagnosis of melanoma and may also lead to undetected or late detection of skin cancers increasing morbidity and mortality in the worldwide population (1,4). Finally, following the reduction of consultations for skin cancer screening during the pandemic period the implementation of screening campaigns and people information in order to increase the awareness of this public health problem should be considered (5).…”
Section: Letter To the Editormentioning
confidence: 99%
“…Patient compliance towards scheduled but deferable visits also reportedly contributed to these totals 5 . For skin cancer, the total number of lesions diagnosed and treated during lockdown periods decreased, with clinical priority given to tumors with high-risk histopathological features 6 , 7 , 8 , 9 . To date, we could not find any studies reporting outcomes for skin cancer patients affected by COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical observations suggest that COVID-19 lockdown periods have caused disruptions in skin cancer care. There has been a substantial decrease in the number of skin cancers diagnosed 6 , 7 , 8 , 9 , 43 , 44 , and treated 8 , 9 , 45 during lockdown ( Table 2 ). In the United Kingdom (U.K.), a prospective cohort study of 2050 patients found a 27‐47% weekly decrease in the number of NMSC treated during their COVID-19 lockdown period (16 th of March-14 th of June 2020) 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…COVID-19 and melanoma surgery in a dermooncology centre in Italy doi: 10.1111/ced.14675 Dear Editor, We have read with great interest the scientific literature regarding the diagnosis and treatment of skin cancer during the COVID-19 pandemic. [1][2][3][4][5] The resulting cancellation of routine dermatological visits could lead to the risk of neglecting cutaneous melanoma (CM), with potential consequences in terms of morbidity and mortality, 1,2 even though the specific impact of the pandemic on CM has yet to be estimated.…”
mentioning
confidence: 99%